BO‘LAJAK JISMONIY TARBIYA O‘QITUVCHILARIDA KASBIY TAFAKKURNI SHAKLLANTIRISH UCHUN PEDAGOGIK KOMPONENTLAR - Erkaboyev, O.M. (SCIENCE and SOCIETY, 2025)
This article analyzes the issue of using pedagogical components of learning in the process of forming the professional thinking of future physical education teachers. During the research, special attention was paid to the specific features and professional orientation of this specialty. Effective methods for training specialists in the field of education are proposed for the purpose of developing thinking skills necessary for successful professional development in the future.
Keywords: education; professional thinking; levels of development; pedagogical component; method